Gestion concertée de l'environnement : Itinéraire vers des engagements volontaires forcés - Arama Yannick; Fabienne Kervarec; Mattheiß Verena (VertigO)
This article deals with the ability of stakeholders to coordinate their actions so that they may solve an environmental issue. From the whole of our case study, we chose to particularly consider the procedural policies which are organized around a local participatory multi-stakeholder process. Those policies are based on a volunteer implementation of agreements on biodiversity and water management. Our observations and analysis of the participatory processes show that consultation is not only made of cooperative interactions between the actors so as to get to a consensus.